2017
DOI: 10.5603/kp.a2017.0037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between fractional flow reserve and visual assessment for moderate coronary artery stenosis

Abstract: A b s t r a c tBackground: Fractional flow reserve (FFR) is an interventional diagnostic method, based on intracoronary pressure measurement, used for the assessment of the severity of coronary artery stenoses. Aim:Our study aimed to compare visual measurements made by multiple observers with FFR measurement in the assessment of angiographically moderate coronary artery stenosis. Methods:The angiographic images of moderate coronary artery lesions of 359 patients enrolled in the study were interpreted independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Similarly, in a study conducted by Bilge et al 21 to determine whether results similar to FFR can be obtained with visual assessment conducted with 3 observers independent from each other, interestingly, there was statistically significant differences exist between the individual results of observers and the FFR result.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, in a study conducted by Bilge et al 21 to determine whether results similar to FFR can be obtained with visual assessment conducted with 3 observers independent from each other, interestingly, there was statistically significant differences exist between the individual results of observers and the FFR result.…”
Section: Discussionmentioning
confidence: 78%
“…We read with great interest the article written by Duran Karaduman et al, titled "Comparison between fractional flow reserve and visual assessment for moderate coronary artery stenosis", published in a recent issue of Kardiologia Polska [1]. The authors can be congratulated for their results, succeeding in demonstrating that in angiographically moderate coronary artery lesions, functional assessment using fractional flow reserve (FFR) is superior to visual estimation of stenosis severity.…”
Section: University Of Medicine and Pharmacy Tirgu Mures Romaniamentioning
confidence: 80%
“…A French registry confirmed that FFR led to treatment reclassification in 43% of patients, with similar MACE rates at one year in 464 reclassified patients as in 611 non-reclassified ones (MACE, 11.2% vs. 11.9%, log-rank p = 0.78) [4]. Therefore, in our opinion, in the study of Duran Karaduman et al [1] it would be interesting to present and discuss the influence of FFR in guiding the therapeutic decision in patients with multivessel disease presenting one or more moderate coronary lesions, and to show if use of FFR in moderate lesions led to any change in the revascularisation strategy or to any reclassification of lesion severity in these cases.Another issue that was only partially addressed in the manuscript, in our opinion, refers to the location of the lesions. The index coronary artery was the left anterior descending artery (LAD) in 68.7% of the cases.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…While early benefits of FFR guidance were observed in patients undergoing conservative management, a trend towards long-term benefits of FFR guidance was also observed in patients undergoing coronary revascularization with numerical mortality differences emerging after 1 year. Since previous studies demonstrated overor underestimation of coronary lesions using angiographic guidance (30,31), FFR guidance allowed improved identification of stenotic coronary lesions with or without functional significance (3). Therefore, early benefits of FFR-based deferral of revascularization observed in our study might be attributed to a reduction of unnecessary revascularization compared to isolated angiographic guidance (6) thus potentially reducing the early risk of bleeding and stent-related complications.…”
Section: Ffr and Mortality Benefits In Real-world Patientsmentioning
confidence: 99%